Mesoporous carbon with large pores as anode for Na-ion batteries - Liu, J. (Science in China Press/Zhongguo Kexue Zazhishe, 2014)
Sodium ion (Na+) batteries have attracted increased attention for energy storage owing to the natural abundance and low cost of sodium. Herein, we report the synthesis of mesoporous carbon with large pores as anode for Na-ion batteries. The mesoporous carbon was obtained by carbonization and dense packing of 50 nm resorcinol and formaldehyde spheres synthesized through an extension Sto¨ber method. Our work demonstrates that replacement of lithium by sodium using large pore carbon as anode might offer an alternative route for rechargeable batteries.